Prevalence for Identification ofLearnerswithCertainLearning DisordersatElementary Grade: A Caseof Province of Punjab - Sumera Firdos، Kiran Shehzadi، Saif Ullah (JIE, 2023)
Students with certain Learning Disorders in Punjab at elementary were the focus of this study. Regarding speaking, reading, writing, and mathematics for students with learning impairments, there may be difficulties. Students with certain Learning Disordersin Punjab were the focus of this study. Students at Punjab’s elementary schools were the focus of the study.